IMPROVING THE ABILITY LISTENING ENGLISH THROUGH AUDIO-VISUAL COMMUNICATION FOR STUDENTS OF THE SEVENTH GRADE IN UPTD SMP NEGERI 1 GILIRENG (CLASS ACTION RESEARCH) - Uleng, Besse (Prodi Pendidikan Bahasa Inggris, FKIP, LP3M Universitas Muhammadiyah Sidenreng Rappang, 2024)
Improving English Listening Skills Through Audio-Visual for Class VII Students of UPTD SMP Negeri 1 Gilireng. Academic Year 2021/2022.This research was carried out at the UPTD of SMP Negeri 1 Gilireng in Class VII where the students' ability to listen to English was quite low. The purpose of writing this classroom action research is to find out whether the Audio-Visual learning model can increase student activity and learning achievement. The data collection methods are observation and learning achievement tests. The data analysis method is descriptive for both qualitative data and quantitative data. The results obtained from this research are that Audio-Visual can improve activities and student learning achievements. This is evident from the results obtained in Cycle I which was 6.3 for learning achievement. From Cycle I to Cycle II it rose to 7.9 for learning achievement. The conclusion obtained from this research is that the Audio-Visual learning model can improve learning achievement.